2013
DOI: 10.1021/jp401017u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms for Adsorption in Cu-BTC Metal Organic Framework

Abstract: We use molecular simulations to analyze the preferential adsorption sites of molecules that differ in size, shape, and polarizability in Cu-BTC metal organic framework. The cage system of the framework can be exploited to enhance adsorption of small gases. We find that nonpolar molecules adsorb preferentially in the small tetrahedral cages, whereas alcohols and water molecules adsorb close to the copper atoms in one of the big cages. Blocking potentially enhances selective adsorption and separation and we ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 69 publications
(90 reference statements)
5
107
1
Order By: Relevance
“…Moreover, inside the MOF, two different types of IL ion pairs are formed: One ion-pair structure exhibits enhanced interionic interactions by strengthening the hydrogen bonding between the cation and anion, whereas the other structure PXRD patterns of (a) IL confined in CuBTC, and (b) pristine CuBTC. 34 Therefore, a lower number of water molecules is available for the coordination of the Cu atoms and hence the appearance of a peak at 11.1° 2θ.…”
Section: Confinement Of Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inside the MOF, two different types of IL ion pairs are formed: One ion-pair structure exhibits enhanced interionic interactions by strengthening the hydrogen bonding between the cation and anion, whereas the other structure PXRD patterns of (a) IL confined in CuBTC, and (b) pristine CuBTC. 34 Therefore, a lower number of water molecules is available for the coordination of the Cu atoms and hence the appearance of a peak at 11.1° 2θ.…”
Section: Confinement Of Ilmentioning
confidence: 99%
“…[34][35][36][37] The present paper reports a systematic study of confined molecular solvents in a MOF. The solvents of interest are acetone, isopropanol, methanol, and the IL 1-ethyl-3-methylimidazolium ethyl sulfate (EMIM-ETS).…”
mentioning
confidence: 99%
“…Van Assche et al (2013) reported the well-pronounced two-step adsorption isotherms of small alcohols (methanol and ethanol) on Cu-BTC, owing to the sequential adsorption behavior of the adsorbates. Jose et al (Jose Gutierrez-Sevillano et al, 2013) suggested the blockage of polar cages by using ionic liquids that could enhance the alcohol adsorption over Cu-BTC in aqueous mixtures. On the basis of Jose's work, Gutierrez-Sevillano et al (2013) shielded the metal sites of Cu-BTC with acetone and dimethyl ether to restrict water attack, and reported it could offer higher ethanol selectivity than the bare framework.…”
mentioning
confidence: 99%
“…Due to the properties of the LPG, the change in the refractive index of the whole film induced by the presence of the analyte can be observed in the transmission spectrum (28). Among the variety of MOFs, thin film of HKUST-1 is considered to be highly selective for CO2 sensing due to the presence of unsaturated copper (II) metal centres and its structure, which consists of two large central cavities (9 Å) surrounded by smaller 5 Å cavities (45).…”
Section: Introductionmentioning
confidence: 99%